INDIKASI MANAJEMEN LABA DI SEKITAR PERUBAHAN PERATURAN PERPAJAKAN TAHUN 2000 - Yuliarini, Sarah (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2005)
The previous research found empirical evidences about earnings management surrounding Initial Public Offering (IPO). This study obtained to give prove that tested earnings management around taxation role changed in companies that listed 1999 untill 2000. Statistical analysis method used is parametric and by comparing of mean of discretionary accruals as a proxy by earnings management. This research ' result shows there are not indication of earnings mangement at one year before legalized taxation change , neither at legalization. It can explain that management have another efford to protecting their asset from government regulation.